Towards Artificial Intelligence by Knowledge and Capability to Lead Rural Development Processes : Finnish Food Authority, Rural Areas Division and the Development Subsidy - Kätkänaho, Helena (My University, 2026)
Government policies can promote support and activities for rural areas and innovative technology. AI Act game into force 1st of August 2024 by European Union. Finnish Food Authority (FFA) in Finland has one unique status and function because it has Rural Areas Division (Paying Agency) which has started when 1st of January 2007. The main responsibility for agency was implementation of agricultural policy in Finland by digitalizing e-services for agricultural and rural development support and further agricultural policy period and CAP (Common Agricultural Policy). Since beginning of 2019 merged Finnish Food Authority (FFA) started, and authority use the name Ruokavirasto in Finnish. Now Rural Areas Division is taking care of implementation of agricultural and rural development subsidies and funds more than 2 billion euros of European Union and national subsidies annually. The objective of this study is impacts of artificial intelligence (AI) in public sector case study organization and to analyses new CAP-strategy 2023-2027 and Rural Areas Division implementation processes. Aim is to provide present information about FFA artificial intelligence (AI) situation and expectations in organization based on strategies and regulations. Further on, narrowed focus is to study technical assistance as one subsidy type in Hyrrä-online webservice software development by DevOps process for regional customers. This qualitative case study focused on FFA AI network data, literature reviews and on collecting AI efforts by theme interviews. Research theory is based on understanding AI, public sector services, process-es and AI capability, knowledge, lean management and continuous improvement to enhance and develop case organization future AI management, vision steps and build AI capability by utilization models. Results show that we need to go towards generative AI step-by-step and start with AI strategy goals, AI knowledge and capability creations, data quality and proper education. In addition to this, we can develop different levels of customer-friendly web services by continuous improvement (CI) and grow individual and team AI learning skills and open discussion. It is important to reach impacts of AI with chosen suitable AI tools for customers, recognize AI risks, ethics and AI possibilities in public sector as well as recognition and guides with common administrative processes, quality data. Active AI networks besides research, common development projects, pilots, impacts of subsidies and innovations could be future research themes.

Hallituspolitiikat voivat edistää ja luvata tukea maaseudun kehittämiselle ja innovatiivisille teknologioille. Euroopan Unionin tekoälyasetus astui voimaan 1.8.2024. Suomesta löytyy ainutlaatuinen virasto, jonka asema ja toiminnot Suomen ainoana maksajavirastona aloitettiin 1.1.2007 Maaseutuvirastona. Viraston vastuulla on muun muassa maataloustukien ja maaseudun kehittämistukien ja kehittämisohjelmien ja CAP-strategian toimeenpanon digitalisaatio ja sähköisten asiointipalveluiden tuottaminen asiakkaille. Vuoden 2019 alusta Maaseutuvirasto fuusioitui Ruokavirastoksi, jonka yhteydessä jatkaa maaseutulinja. Maaseutulinja toimii edelleen Suomen maksajavirastona, huolehtien maatalous-, markkina- ja maaseudun kehittämisen tukien toimeenpanosta ja yli kahden miljardin euron vuotuisten EU- ja kansallisten tukimaksujen maksujen maksamisesta. Tämän tutkimuksen tavoitteena on analysoida uuden CAP-strategian 2023-2027 ja maaseutulinjan toimeenpanon tukiprosesseja sekä tarjota tietoa viraston tekoälyn käytöstä, osaamisesta, kyvykkyydestä sekä odotuksista julkisella sektorilla. Tutkimuksessa keskitytään erityisesti yhden tukimuodon: teknisen avun Hyrrä-verkkopalvelun toimeenpanon ja tekoälyverkoston prosessiin. Tutkimustietoa kerätään tekoälyponnisteluista teemahaastatteluin. Laadullinen tapaustutkimus etsii vastauksia tutkimuskysymyksiin teemahaastettaluiden, käsitteiden ja kirjallisuuskatsauksien avulla. Asiasanoina tutkimuksen keskiössä olevat kyvykkyys, tietämys, leanaus ja jatkuva parantaminen. Ne kuvaavat kehitysaskeleita Ruokaviraston tekoälyvision ja kyvykkyyden rakentamiseen sekä tulevaisuuden tekoälyn hyödyntämiseen liittyvien mallien luomiseen. Taustalla vaikut-tavat organisaation rakenne, strategia, ydinprosessit, vahvuudet, mahdollisuudet, esteet, tiedot, taidot tai koulutus käyttää generatiivista tekoälyä. Tutkimustulokset osoittavat, että kohti generatiivisen tekoälyn käyttöä on hyvä edetä vaiheittain. Tekoälystrategian tavoitteiden kautta voi luoda tekoälytietämystä ja saavuttaa kyvykkyyksiä, kun panostetaan tiedon laatuun sekä sopivaan koulutukseen. Lisäksi voimme luoda eri tasoisia asiakasystävällisiä verkkopalveluita jatkuvan parantamisen avulla, lisätä yksilöiden ja ryhmien tekoälyn osaamistaitoja sekä avointa keskustelua. Tärkeää on luoda asiakkaille vaikuttavuutta sopivien tekoälyvälineiden turvin. On tunnistettava tekoälyyn liittyviä riskejä, etiikkaa ja tekoälymahdollisuuksia julkisella sektorilla. Yhteiset hallinnolliset prosessit, laadukas data, tekoälyverkostot, ohjeistukset, yhteiset kehittämisprosessit ja aktiivinen tutkimus- ja innovaatiotoiminta, projektit, pilotit ja tukien vaikuttavuus ovat tärkeitä tulevaisuuden tekoälyn tutkimusteemoja.
Keywords: agricultural policy; planning of rural areas; capability; rural development; knowledge; artificial intelligence; public authority; strategy work; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management